HUBUNGAN PANJANG DAN BOBOT IKAN NILA LOKAL, BEST F5 DAN F6 DI PANGKEP, SULAWESI SELATAN PADA UMUR 60 HARI PEMELIHARAAN - Kusmini, Irin Iriana; Gustiano, Rudhy; Putri, Fera Permata (BERITA BIOLOGI, 2014)
Best tilapia is breed fish developed by Research Center and Development of Freshwater Aquaculture (BPPBAT) Bogor that has been launched since 2008. Best tilapia is the third generation of gift tilapia. In order to obtain a better growth performance, BPPBAT continued the process of breeding, and to date we have obtained the sixth generations of Best tilapia. This study was aimed to determine growth of tilapia through observation of the relationship between the length and weight of local tilapia, F5 and F6 BEST which were maintained in brackish waters in the Pangkep area, South Sulawesi. Fish samples were taken at random, 30 fishes were taken from each population for length and weight measurement. Calculation of the length-weight of fish in the Pangkep area obtained regression coefficient (b) for local fish 2.4361; BEST F5 3.1077 and F6 3.0522. These values indicated that the local tilapia was negatively allometric while BEST was positively allometric, with local fish condition factor ranged between 0.471-1.334, F5; 0.468-1.479 and 0.498-1.534 F6 respectively. This results has indicating the normal condition of the fish. The length-weight relationship of fish had a value of determinant (R 2) ranged from 0.7829-0.9182, and indicated fish variations influenced by other variables was rather small and has suggested close relationship between length and weight.